THE INSTITUTE OF ADOPTION IN TNE REPUBLIC OF KAZAKHSTAN AND THE CONSTITUTIONAL RIGNTS OF ADOPTED CHILDREN (Journal of actual problems of jurisprudence, 2024)
Adoption is the legal adoption of a child into a family. A child as a relative acguires whether son or daughter all rights and obligations. Parents thereby acguire the highest responsibility for the child and his full development. The article talks about the importance of the institution of adoption, that in our state great attention is paid to the priority of family education, and for children who have fallen into care, such an educational facility can only be provided by the institute of adoption. At the same time, the adoption of children is always a very complicated legal procedure. This is due to the fact that this issue is very important and, depending on the child's prospects, places great responsibility on the state and parents.A number of problems in the process of adoption about the peculiarities of the adoption of Kazakhstani children by foreign adoptive parents, including from same-sex families is described by the authors. The difficulties of monitoring adopted children, especially those adopted by foreign citizens, are described. Therefore, it is concluded that main task is the protection of children's rights. The issues of adoption of disabled children, protection of their rights is also touched upon.Keywords: law; family; orphan; Constitution; convention.